PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA SMART BOOK BERBANTUAN BOOK CREATOR TINGKAT SMP DITINJAU DARI SEGI KEVALIDAN - Jamiatun Nasikhah; Athar Zaif Zairozie; Darwin Djeni (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to produce a smart book mathematics learning media assisted by a valid book creator at the junior high school level. This research uses development research (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data collection was carried out using a questionnaire technique. The results of the analysis of the media expert's assessment have an average score of 95.5 which means the media is declared in the valid category by media experts. The results of the analysis of the material expert's assessment have an average score of 94 which means the media is declared in the very valid category by material experts.